2008
DOI: 10.1509/jmkg.72.4.012
|View full text |Cite
|
Sign up to set email alerts
|

When Does Guanxi Matter? Issues of Capitalization and Its Dark Sides

Abstract: When Does Guanxi Matter? Issues of Capitalization and Its Dark SidesGuanxi refers to the durable social connections and networks a firm uses to exchange favors for organizational purposes. This study examines how and when guanxi operates as a governance mechanism that influences firm marketing competence and performance in the transitional economy of China. Drawing on social capital theory, the authors propose an integrative framework that unbundles the benefits and risks of guanxi and delineates the organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
363
3
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 400 publications
(381 citation statements)
references
References 71 publications
13
363
3
2
Order By: Relevance
“…A well-documented phenomenon in China is called guanxi, including diversified relationships. Guanxi is best described as a trust-building system of social capital and interpersonal connections (Gu et al, 2008) that acts as a lubricant to business activities (Ramasamy, Goh, & Yeung, 2006). It has been suggested that guanxi has even begun to supplant the role of traditional Chinese families (Chow & Ng, 2004).…”
Section: Leaders' Social Ties In Chinamentioning
confidence: 99%
See 4 more Smart Citations
“…A well-documented phenomenon in China is called guanxi, including diversified relationships. Guanxi is best described as a trust-building system of social capital and interpersonal connections (Gu et al, 2008) that acts as a lubricant to business activities (Ramasamy, Goh, & Yeung, 2006). It has been suggested that guanxi has even begun to supplant the role of traditional Chinese families (Chow & Ng, 2004).…”
Section: Leaders' Social Ties In Chinamentioning
confidence: 99%
“…Second, government ties provide firms with exclusive access to information related to the country's changing policies, industrial development plans, and governments' policy intents (Sheng et al, 2011). As Gu et al (2008) noted, guanxi with government officials helps managers to gain valuable information about the environments such as policy shifts and industry reforms, increasing firms' responsiveness to changing environments. Finally, leaders' government ties can increase the legitimacy of a firm-the extent to which the firm's actions are perceived as trustable and desirable by stakeholders.…”
Section: Leaders' Social Ties In Chinamentioning
confidence: 99%
See 3 more Smart Citations